Abitare il margine, raccontare luoghi invisibili: le autobiografie dei detenuti per mafia nella Casa Circondariale Catania Bicocca - Bitto, Giulia (EtnoAntropologia, 2022)
This paper aims to explore the theme of the perception and experience of peri-urban and marginal places through the autobiographies written by mafia inmates in the Catania Bicocca Prison, who have joined a project I started inside the prison in the context of ethnography of detention. In the first part of this work, the notion of a peri-urban place is presented, to understand the context in which the prisoners lived. Subsequently, the Catania metropolitan area is analyzed in detail; finally, the experience and perception of these places of life are examined by following the stories of the prisoners.